Curcumin protects against failure to generate a transmembrane potential and protein aggregation of rat liver mitochondria induced by tert-butylhydroperoxides (Faculty of Medicine Universitas Indonesia, 2007)
Curcumin, an active ingredient of curcuma plant has been thought to be beneficial in the treatment of liver diseases. In the previous studies, we have shown the protective effects of curcumin against lipid peroxidation and swelling of the ratlivermitochondrial preparation induced by tert-butylhydroperoxide (t-BuOOH). In the present study, the administration of t-BuOOH of 90 µM caused the mitochondria failed to generate a transmembrane potential (Ym). Of 3 doses of curcumin administered (0.5µM, 2.5 µM dan 5.0 µM) the maximum protective effect against failure to generate a transmembrane potential caused by t-BuOOH was obtained by 2.5µM of curcumin(79.13+6.28%).Further, curcumin of 1000 µM could prevent protein aggregation formation caused by t-BuOOH in the electrophoretogram. This study shows the protective effects of curcumin against damaged of energy production system and protein of the mitochondria caused by t-BuOOH. (Med J Indones 2007; 16:139-45)